Traumatic Gallbladder Perforation in Children – Case Report and Review - Le, Melanie Thanh Phuong; Herrmann, Jochen; Groth, Michael; Reinshagen, Konrad; Boettcher, Michael (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Background Gallbladder perforation is a very rare finding in children. Clinical and radiografic presentations are often vague. Hence it is a challenging diagnosis, often missed during initial evaluation with potentially fatal consequences. The aim of this case report and review was to identify factors that might help to diagnose and manage future cases.Methods We present a case of gallbladder perforation in an 8-year-old child after blunt abdominal trauma caused by a handlebar in which imaging modalities such as ultrasound and magnetic resonance imaging (MRI) helped us to determine proper management. We identified and evaluated comparable cases for isolated traumatic gallbladder injury. A review of the recent literature was performed by online search in Pubmed and Google Scholar using “gallbladder injury in children”, “gallbladder perforation children”, “blunt abdominal trauma children” as keywords. We focused on articles exclusively in the pediatric section. The literature from the period 2000–2020 was taken into account to review the state of the art in diagnosis and management.Results and Conclusion Recent literature for gallbladder injury in pediatrics is sparse compared to the adult counterpart. Only eight published cases of isolated gallbladder injury in children were identified. Since the onset of symptoms may not develop acutely and often develops in an indistinct manner, radiografic examinations play an important role in the diagnostic progress. The authors advise caution in cases of blunt abdominal trauma especially involving handlebars, intraperitoneal free fluid, and severe abdominal pain. We advocate high suspicion of gallbladder perforation if the gallbladder wall displays discontinuation or cannot be definitively differentiated in sonografic examination. Echogenic fluid within the gallbladder should always lead to suspicion of intraluminal bleeding. Repeated clinical and imaging examinations are mandatory since the onset of signs and symptoms may be delayed.Key Points: Citation Format
Keywords: traumatic gallbladder injury in children; gallbladder perforation; handlebar injuries